2014
DOI: 10.1007/s10955-014-1014-y
|View full text |Cite
|
Sign up to set email alerts
|

Sub-exponential Mixing of Open Systems with Particle–Disk Interactions

Abstract: We consider a class of mechanical particle systems with deterministic particle-disk interactions coupled to Gibbs heat reservoirs at possibly different temperatures. We show that there exists a unique (non-equilibrium) steady state. This steady state is mixing, but not exponentially mixing, and all initial distributions converge to it. In addition, for a class of initial distributions, the rates of converge to the steady state are sub-exponential.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We prove that the Markov process generated by the generalized KMP model has a mixing rate ∼ t −2 and a convergence rate ∼ t −1 to the NESS. The closest related results we know are the slower-than-exponential convergence to the NESS in [38,37,8,9] and the polynomial convergence to the equilibrium in [25]. In addition to the upper bound of convergence, we also showed that the speed of convergence to NESS has a lower bound t −1−γ for any γ > 0.…”
Section: Introductionsupporting
confidence: 55%
“…We prove that the Markov process generated by the generalized KMP model has a mixing rate ∼ t −2 and a convergence rate ∼ t −1 to the NESS. The closest related results we know are the slower-than-exponential convergence to the NESS in [38,37,8,9] and the polynomial convergence to the equilibrium in [25]. In addition to the upper bound of convergence, we also showed that the speed of convergence to NESS has a lower bound t −1−γ for any γ > 0.…”
Section: Introductionsupporting
confidence: 55%
“…We refer readers to Section 5 and Section 6 for more engaged discussion about microscopic heat conduction models and their connections to deterministic dynamical systems. Besides these two models, other microscopic heat conduction models that have subexponential mixing rate include the particle model in [50,49], the rotor model in [9,10], and the anharmonic chain in [21]. Other examples of sub-exponential rate of convergence have also been observed in various models like MCMC algorithms and random walks [26,47,36].…”
Section: Introductionmentioning
confidence: 99%
“…Under certain assumptions, these models can be described by stochastic differential equations, and results that include the existence and uniqueness of nonequilibirum steady states have been shown [3], as have exponential convergence and other statistical properties [16,17]; see also [1]. A second group consists of results for Hamiltonian models similar to those in [4], with additional assumptions or special features to make the problem more tractable (as noted earlier, Hamiltonian models are much harder), they include: [2,20], which prove ergodicity of the invariant measure assuming existence; [9], which proves existence and uniqueness for a model in which all energy exchanges are exclusively with 'thermostats' (or heat baths); and, [21], which treats a model with special geometry. A third group of results we know of consists of [10] and variants of this model [11,15].…”
Section: Introductionmentioning
confidence: 99%